Characterization of the translation elongation factor 1‐αgene in a wide range of pathogenicAspergillusspecies. Issue 4 (April 2017) - Nouripour‐Sisakht, Sadegh; Ahmadi, Bahram; Makimura, Koichi; de Hoog, Sybren; Umeda, Yoshiko; Alshahni, Mohamed Mahdi; Mirhendi, Hossein
Abstract : Purpose. : We aimed to evaluate the resolving power of the translation elongation factor (TEF)‐1 α gene for phylogenetic analysis of Aspergillus species. Methodology. : Sequences of 526 bp representing the coding region of the TEF‐1α gene were used for the assessment of levels of intra‐ and inter‐specific nucleotide polymorphism in 33 species of Aspergillus, including 57 reference, clinical and environmental strains. Results. : Analysis of TEF‐1α sequences indicated a mean similarity of 92.6 % between the species, with inter‐species diversity ranging from 0 to 70 nucleotides. The species with the closest resemblance were A. candidus / A. carneus, and A. flavus / A. oryzae / A. ochraceus, with 100 and 99.8 % identification, respectively. These species are phylogenetically very close and the TEF‐1α gene appears not to have sufficient discriminatory power to differentiate them. Meanwhile, intra‐species differences were found within strains of A. clavatus, A. clavatonanicus, A. candidus, A. fumigatus, A. terreus, A. alliaceus, A. flavus, Eurotium amstelodami and E. chevalieri . The tree topology with strongly supported clades (≥70 % bootstrap values) was almost compatible with the phylogeny inferred from analysis of the DNA sequences of the beta tubulin gene (BT2). However, the backbone of the tree exhibited low bootstrap values, and inter‐species correlations were not obvious in some clades; for example, tree topologies based on BT2 and TEF‐1α genes were incompatible for some species, such as A. deflectus, A. janus and A. penicillioides. Conclusion. : The gene was not phylogenetically more informative than other known molecular markers. It will be necessary to test other genes or larger genomic regions to better understand the taxonomy of this important group of fungi.